2012
DOI: 10.1007/s00723-011-0309-2
|View full text |Cite
|
Sign up to set email alerts
|

Nontargeted NMR Analysis To Rapidly Detect Hazardous Substances in Alcoholic Beverages

Abstract: Nuclear magnetic resonance spectroscopy is introduced for the analysis of alcoholic beverages in the context of governmental health and safety control. For sample preparation of all types of alcoholic beverages, only addition of buffer is required as single step. To detect potentially unsafe samples especially in the context of unrecorded alcohol (i.e., illegally or informally produced alcohol), a nontargeted approach based on principal component analysis (PCA) was applied. The PCA scores plot of 304 samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…For example, PCA and cluster analysis are often applied to detect outliers and for exploratory analysis of the data [36][37][38][39]. Based on this preliminary investigation, it can be decided if the application of more advanced multivariate approaches aiming at discrimination or prediction of analytical parameters is reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…For example, PCA and cluster analysis are often applied to detect outliers and for exploratory analysis of the data [36][37][38][39]. Based on this preliminary investigation, it can be decided if the application of more advanced multivariate approaches aiming at discrimination or prediction of analytical parameters is reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…After application of two dummy scans, 128 scans were collected into a time domain of 131 072 (131 K) complex data points using a 20.5503 ppm spectral width and a receiver gain of 101. The acquisition time was set to 7.96917 s and the recycle delay was 4 s. Sample preparation and acquisition parameters for 1 H NMR measurements of alcoholic beverages were detailed in the previous publications . The NMR data were acquired automatically under the control of ICON‐NMR (Bruker Biospin, Rheinstetten, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been successfully used to detect unknown contaminants in potable water, 36 carbonated 37 and alcoholic 38,39 beverages. In particular, Charlton et al 36 demonstrated that NMR spectroscopy is an ideal technique for the non-targeted detection of unknown contaminants, showing that mixtures of pesticides, industrial solvents, toxins and explosives could be identied under the same experimental conditions.…”
Section: -35mentioning
confidence: 99%